Public debt, budget deficit and tax policy reforms for fiscal consolidation in Sri Lanka: rationale and feasibility - Vinayagathasan, Thanabalasingam; Sri Ranjith, Jothiratne Ganithage (National Science Foundation: Colombo, 2021)
This paper aims to examine the rationale and feasibility to minimise the budget deficit that maintains the public debt at manageable level without retarding economic growth. Accumulation of government debt may subsequently shape future budget deficit via policies aimed at deficit reduction. Government authorities substantiate austerity and deficit reduction arguing for a case of sustainable fiscal policy. Hence, this study investigates the relationship between public debt, budget deficit and tax policy reforms for fiscal consolidation in Sri Lanka for the period 1990-2019. The study found that direct tax revenue, indirect tax revenue, real GDP and consumer price index are negatively correlated with government debt to GDP ratio in the long run, while in the short run, only direct tax revenue affects it significantly. Whereas, government expenditure, budget deficit, lending interest rate and exchange rate have positive and statistically significant impact on government debt to GDP ratio in the long run, while only exchange rate affects it significantly in the short run. This study identified unidirectional causality relationship between GE and PD, TRD and PD, TRID and PD, RGDP and TRD, RGDP and EXR, CPI and TRD, CPI and TRID and bilateral causality between RGDP and TRID. Findings of this study suggest that there is a rationale and feasibility to achieve fiscal consolidation in Sri Lanka by tax policy reforms and adjustments of government expenditures. The necessity of tax reforms is reflected by the greater potentials of direct taxes over the indirect taxes to contribute for public debt reduction, both in the short run and long run.
Keywords: Budget deficit; Public debt; Tax policy reforms; Revenue-based fiscal consolidation